Building Safe and Inclusive Schools: Enhancing Anti-Bullying Awareness Based On The Sustainable Development Goals (SDGs) Agenda At MAN 2 Cianjur - Septiyana, Iyan; Mellani; Sani, Talitha Azmi (Universitas Muhammadiyah Surakarta, 2025)
Bullying in schools is a social phenomenon that occurs throughout Indonesia, including in Cianjur Regency, West Java Province. Quality Education is part of the UN Sustainable Goals agenda that required to be implemented by member states, including Indonesia. The priority issue underlying this activity is the continued prevalence of bullying due to a lack of understanding and knowledge about the SDGs. As a solution, the community service team held a public lecture and workshop with the theme